Middlesex - Eugenides, Jeffrey (2002)
Calliope's friendship with a classmate and her sense of identity are compromised by the adolescent discovery that she is a hermaphrodite, a situation with roots in her grandparents' desperate struggle for survival in the 1920s.
Keywords: Domestic fiction; Greek Americans -- Fiction; City and town life -- Fiction; Suburban life -- Fiction; Detroit (Mich.) -- Fiction